Analysis Of Land Use Change And Its Impact On Carbon Stock Availability In Katobu District, Muna Regency - Wa Ode Lasmi Putri M; Kahirun; Gandri, La; Erif, La Ode Muhammad (University of Jember, 2025)
This study aims to determine land use change and the extent of its impact on carbon stock changes due to land use change in Katobu District, Muna Regency. This research was conducted from July to August 2023. In this study, an analysis was carried out to assess the extent of land use change in 2016 and 2022, accompanied by an analysis of the carbon stock generated from land use during that period using the formula from the GHG Calculator developed by ICLEI–Local Governments for Sustainability. The results of the study show that there are five types of land with the largest percentage being Mixed Agriculture at 65% in 2016 and 43% in 2022, while the highest carbon stock value in 2016 was Mixed Agriculture with 22,046.7 tons and the highest carbon stock value in 2022 was also Mixed Agriculture with 14,846.7 tons.